A NEW APPROACH TO TEACHING HYDRAULICS IN ENGINEERING FIELDS - Azizbek Asomiddinovich Khojimatov (Modern American Journals, 2025)
This article presents ideas on organizing new experimental work using modern equipment and analyzing the results in teaching hydraulics.
Keywords: Experiment, flow, reversal, pipe, steady flow, meter, piezometer, excess air, irrigation system, chemical industry, agricultural industry, machinery, pump, compressor.